A traveled first lady : writings of Louisa Catherine Adams - Adams, Louisa Catherine, 1775-1852 (The Belknap Press of Harvard University Press, 2014)
Congress adjourned on 18 May 1852 for Louisa Catherine Adams's funeral, according her an honor never before offered a first lady. Telling the story of her own life, juxtaposed with rich descriptions of European courts, Washington political maneuvers, and the continuing Adams family drama, Louisa Catherine Adams demonstrates why she was once considered one of the preeminent women of the nineteenth century.